PENGARUH KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN PADA HUBUNGAN ANTARA PARTISIPASI ANGGARAN DAN KINERJA MANAJERIAL (Studi Empiris pada BPR di Bali) - Yogantara, Komang Krishna; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
The purpose of this research to demonstrate empirically the effect of budget participation on managerial performance in which variable organizational leadership style and commitment as moderating variable on BPR in Bali. The data was collected by questionnaire method to scale (measure) participatory budgeting, organizational commitment, leadership style, managerial performance. Examination hypothesis used were moderate analisys regression (MRA). The result of the test showed that organizational commitment does not moderate the relationship between budgetary participation and performance. Leadership style does not moderate the relationship between budgetary participation and performance.   Keywords: Style of Leadership, Organizational commitment, Managerial performance, Budget participation